A Habitat and a Parasite : Adult and Larval Parasitic Freshwater Mussels Impact Habitat Choice and Predator–Prey Interactions of a Host Fish and Its Prey - Rock, Sebastian L.; Elmlund, Anna M.; Nilsson, P. Anders ; 0000-0002-3541-9835; Watz, Johan; Calles, Olle; Österling, Martin (Ecology and Evolution, 2025)
Parasitic freshwater mussels are endangered ecosystem engineers with an array of impacts on multiple trophic levels and life stages. While the impacts of adult mussels on separate trophic levels have been studied, few have directly tested how adult mussels can impact trophic interactions, or investigated the impacts of the parasitic mussel larvae (glochidia) on such interactions. We present a laboratory study which mimics two-stream substrates for the endangered thick-shelled river mussel (Unio crassus): one dominated by gravel and one by cobbles. First, the preference of a gammarid (Gammarus pulex) for mussel-dominated habitats was tested in the presence/absence of chemical cues from the predator bullhead (Cottus gobio). Second, the preference of bullhead for mussel-dominated habitats was tested under or without glochidia infestation. Third, the effect of infestation on bullhead predation on gammarids was assessed in the presence of adult mussels. Gammarids only significantly preferred mussel habitats in the absence of predator cues, whereas infested bullhead tended to prefer mussel habitats in cobble substrates. The presence of adult mussels only significantly reduced bullhead predation on gammarids in the gravel habitat, whereas infestation did not affect bullhead predation. Despite gammarids not preferring mussel habitat in the presence of predator cues, mussel beds represent valuable habitat to gammarids as mussel presence can facilitate a reduction of predation by bullhead. Infestation did not affect the rate of bullhead predation on gammarids but did attract bullhead to mussel habitat in cobble substrates. Our results suggest that mussel beds may be valuable habitat for both their host fish and the prey of their hosts, attracting both and increasing predator–prey interactions. This study highlights the cross-trophic mechanisms by which multiple life stages of parasitic mussels can impact the interactions of their surrounding benthic community, underscoring their importance as ecosystem engineers.
Publisher Copyright: © 2025 The Author(s). Ecology and Evolution published by British Ecological Society and John Wiley & Sons Ltd.
Keywords: community ecology; conservation; ecosystem function; endangered species; freshwater; microhabitat; parasitism; Unionida